KORELASI KEWENANGAN PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN (PPATK) DENGAN LEMBAGA PENGAWAS DAN PENGATUR (LPP) TERHADAP TINDAK PIDANA PENCUCIAN UANG - Dian Ayu Victoria Septiana dan Eka Pradata, Cut Nadia Diba Riski (GEMA, 2015)
Bank Indonesia (BI), as the Regulatory and Supervisory InstitutionÂ has the authority and obligation to participate and play an active role in combating money laundering (TPPU), one of which is the existence of so-called principle of know your customer or know your customer principle which is an effort to prevent the entry of the proceeds of criminal acts in the banking industry. Bank Indonesia is actively and continuously coordinating with related agencies such as the Center for Financial Transaction Reports and Analysis Center (PPATK). In the prevention and combating of money laundering, PPATK are to cooperate with related parties are poured with or without some form of formal cooperation, one of which is the Institute of Supervisory and Regulatory (LPP), the body which has the authority to control, regulation, and / or the imposition of sanctions against the complainant